Estimation of the demand function of ration card items in the light of IMF reforms - عبد الحميد, مناهل مصطفى; هادي, اشراق طالب (Journal of Economics and Administrative Sciences, 2019)
The ration card system is a kind of support provided by the state to individuals through the provision of essential goods at subsidized prices during the period of war or crisis. For many years, the ration card was an essential source of food supplies to Iraqis, especially under the economic siege of the nineties, But after the events of 2003 and the passage of Iraq's political and economic changes required radical reforms in the ration card system according to the recipes of the International Monetary Fund. It was evident from the estimation of the demand function that the price did not have the greatest impact on this type of goods because the ration card items are subsidized by the government. There is also a significant decrease in quantities of foodstuffs despite the increase in population. Most of the results have highlighted the large imbalances in the economy. The most important finding of the researcher is the need to work on the development of an integrated production sector in which the great role of the private sector and try to improve in the agricultural sector to be able to fill the local market demand of commodities and competition of imported goods, especially in view of the decline of Iraq's strategic stocks significantly.